A dual-band amplitude shift-keying terahertz encoder based on 2DEG metamaterial. (August 2020) - Shi, Xintong; Zeng, Dehui; Huang, Wei; Yin, Shan; Guo, Ling
Abstract: The amplitude shift keying (ASK) is a significant technique in communications. We propose a terahertz encoder based on the 2-dimensional electron gas (2DEG) metamaterial, which can complete ASK in the 0.43 THz and 0.81 THz independently. The ON/OFF ratio of the encoder in each band is more than 86%. The research is helpful in promoting terahertz technology and next-generation communications.